2013
DOI: 10.1007/s00267-013-0080-2
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of National Park System Visitation: The Efficient Use of Count Data Models, Meta-Analysis, and Secondary Visitor Survey Data

Abstract: The National Park Service (NPS) currently manages a large and diverse system of park units nationwide which received an estimated 279 million recreational visits in 2011. This article uses park visitor data collected by the NPS Visitor Services Project to estimate a consistent set of count data travel cost models of park visitor willingness to pay (WTP). Models were estimated using 58 different park unit survey datasets. WTP estimates for these 58 park surveys were used within a meta-regression analysis model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…We conclude that the estimated value of $62 billion for National Parks is highly credible given that Neher, et al (2013) estimated the recreation use value alone for the National Parks at $28.5 billion. It makes sense that total economic value-which includes recreation use values and passive or non-use values-would be significantly larger.…”
Section: Calculating National Total Economic Value Of National Parks mentioning
confidence: 78%
See 1 more Smart Citation
“…We conclude that the estimated value of $62 billion for National Parks is highly credible given that Neher, et al (2013) estimated the recreation use value alone for the National Parks at $28.5 billion. It makes sense that total economic value-which includes recreation use values and passive or non-use values-would be significantly larger.…”
Section: Calculating National Total Economic Value Of National Parks mentioning
confidence: 78%
“…3 Previous analysis of NPS visitation data using a travel demand method found a median value of $108 per day (Neher, et al 2013). Two other studies also used the travel demand method.…”
mentioning
confidence: 99%
“…We acknowledge this as a possible limitation of our study. 20 Many applied researchers are rather conservative in their assumptions about how much the opportunity cost of time might add to the value of a visited site and preferred to use the lower bounds of the wage rate (Neher et al 2013). For example, Hynes et al (2009) suggested that it would be useful to determine individual opportunity costs of travel time to avoid a potential bias related to assuming an excessively high wage fraction as a reference.…”
Section: Discussionmentioning
confidence: 99%
“…Haefele et al [22] found that the lands, waters, historic sites, and programs of the US National Park System are worth at a minimum $92 billion by using the CE. To estimate more specific economic values of natural resources, Neher et al [25] assessed the recreation use value for the US National Parks at $28.5 billion. A body of research has focused on estimating the use or non-use values of individual parks and natural resources (e.g., Turner and Wilmarth [26], Heberling and Templeton [27], Duffield [28], Douglass and Harpman [29]).…”
Section: Economic Valuation Studies On Protected Areasmentioning
confidence: 99%